Rekontruksi Pengetahuan Inklusif dalam Mewujudkan Scientific Vision Program Studi PGMI UM Magelang - Oktradiksa, Ahwy (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
Inclusion education is an educational concept that does not distinguish the background of a child's life just because of physical and mental limitations. This education is intended for children with special needs to be able to hone their talents and motivations since few of them experience problems in receiving and processing the information around them. Generally, the problem is known as specific learning difficulties (learning disabilities) which is a disorder in one or more of the basic psychological processes covering the understanding and the use of spoken or written language. The department of elementary madrasah teacher education of Islamic education faculty of Muhammadiyah Magelang University (PGMI FAI UMMagelang) is trying to formulate Scientific Vision which is manifested as an explanation in the vision of department which means â€œExcellence in Inclusive Education.â€